Surface stress of gold nanoparticles revisited. (1st August 2021) - Holec, David; Löfler, Lukas; Zickler, Gerald A.; Vollath, Dieter; Fischer, Franz Dieter
Graphical abstract: Highlights: Atomistic modelling provides the shape of nanoparticles. Nanoparticles are spherical-similar solids. A Cauchy-Born model helps to describe the deformation state. A core–shell spherical model provides the surface stress and surface energy. Abstract: The surface energy has been one of the topics of atomistic research for nanoparticles in the last decades. However, the physical role of surface stress and its quantification have been a lot less an object of research. Assumptions for the surface stress, going back to the thermodynamic basis of continua, have been popular. As an example the surface stress (state) follows as derivatives of the surface energy with a rather "classical" evolution equation for the deformation energy. The current concept introduces a combination of atomistic modelling and continuum mechanics for a core–shell system. Considering crystalline and amorphous gold nanoparticles with radii in the range of 1 nm to 12 nm, we are finally able to independently calculate the values of surface stress and surface energy, both slightly decreasing with the increasing particle radius. Surprisingly large values of surface stress are predicted for the case of amorphous nanoparticles.